Business Process Management (BPM) Maturity in Small and Medium Enterprises (SMEs): Systematic Literature Review - Azizah Hadny Qurrota A'yun; Budhi Prihartono (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2025)
Business process is an essential aspect of a company and must be managed continuously using Business Process Management (BPM). To support BPM implementation, many researchers have developed maturity models that can measure the existing implementation and provide improvement roadmaps to a company. However, most of the maturity model research have not taken SMEs’ context into consideration in developing the maturity model even though they have distinct characteristics than large companies. The maturity model that is specifically designed or applied in SME context is scarce and underdeveloped despite the importance of SMEs to developing countries such as Indonesia. This research aims to explore the development of BPM maturity research in SMEs and analyze its research focus and purpose of use, using a systematic literature review method. Based on the result, the research on BPM maturity in SMEs is limited, with only 14 articles since 2005. The number of articles has decreased in the last five years. Most of those articles focused on applying the maturity model in a real-life context and mostly served a descriptive purpose only, thus unable to provide improvement roadmaps for companies. Therefore, further studies should explore this research topic by developing a maturity model of BPM specifically designed for SMEs with a prescriptive purpose of use.